CMS ECAL upgrade for precision timing and energy measurements at the High Luminosity LHC. Issue 1 (1st November 2022) - Reis, Thomas; ,
Abstract : The unprecedented instantaneous luminosity provided by the High Luminosity upgrade of the LHC (HL-LHC) at CERN requires an upgrade of the Compact Muon Solenoid (CMS) electromagnetic calorimeter (ECAL). The barrel region of the CMS ECAL will be preserved but will be operated at a lower temperature and with a completely new readout and trigger electronics. A dual gain trans-impedance amplifier and an integrated circuit providing two 160 MHz analog to digital converter channels, gain selection, and data compression will be used in the new readout electronics. The trigger decision will be moved off-detector and performed by powerful and flexible field programmable gate array processors, allowing for sophisticated trigger algorithms to be applied. The upgraded ECAL will be capable of high-precision energy measurements throughout HL-LHC data taking and will greatly improve the time resolution for photons and electrons above 10 GeV.